Changing Experience and Interpretation of Menarche by Generation - Mishra, Mira (Himalayan Journal of Sociology and Anthropology, 2014)
This note seeks to bring to light women’s subjective experience and interpretation of menarche by generation, links up the changes with changing socio-economic processes and argues that younger Nepali women have relatively concrete information on menstruation than their mothers and grandmothers. DOI: http://dx.doi.org/10.3126/hjsa.v6i0.10713 Himalayan Journal of Sociology and Anthropology Vol.6 2014: 119-133